THE USE OF FRACTION CARD MEDIA TO IMPROVE MATHEMATICS LEARNING OUTCOMES OF GRADE 3 STUDENTS OF YPK ERMASU MERAUKE ELEMENTARY SCHOOL - Babangan, Ida; Rahayu, Dewi Puji; Lamera, Sonya (Cerdas Proklamator, 2024)
ABSTRACT This study aims to improve the mathematics learning outcomes of grade 3 students of SD YPK Ermasu Merauke by using fraction card media. This research was conducted by involving 24 grade 3 students as research participants. The results showed that the use of fraction card media had a positive impact on students' understanding of fractions. This is evidenced by the increase in students' average score from 66.08 in the pre-cycle to 80.07 in Cycle II. In addition, the percentage of students who reached the KKM also increased from 63% in Cycle I to 92% in Cycle II. In addition, students also showed higher interest and participation in learning when using fraction card media. This study concluded that the use of fraction card media can improve students' understanding of the concept of fractions in grade 3 SD YPK Ermasu Merauke. Recommendations for future research are to conduct research with a larger sample and involve other variations of learning media to expand students' understanding of other mathematical concepts. Keywords: fraction cards, math learning outcomes, grade 3 students